(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1913)
The Ruthwell Cross was broken after the Reformation and the fragments were reconstructed at the beginning of the nineteenth century when it was returned to the church. An account is given of the attempts to decipher the inscriptions on the Bewcastle obelisk or cross. Consideration is also given to the likely dates of both monuments.